2021
DOI: 10.1021/acs.joc.1c00510
|View full text |Cite
|
Sign up to set email alerts
|

[(PPh3)2NiCl2]-Catalyzed C–N Bond Formation Reaction via Borrowing Hydrogen Strategy: Access to Diverse Secondary Amines and Quinolines

Abstract: Commercially available [(PPh3)2NiCl2] was found to be an efficient catalyst for the mono-N-alkylation of (hetero)­aromatic amines, employing alcohols to deliver diverse secondary amines, including the drug intermediates chloropyramine (5b) and mepyramine (5c), in excellent yields (up to 97%) via the borrowing hydrogen strategy. This method shows a superior activity (TON up to 10000) with a broad substrate scope at a low catalyst loading of 1 mol % and a short reaction time. Further, this strategy is also succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…Recently, there has been a trend toward utilizing earth-abundant metals to construct N-heterocycles under ligand-free conditions . In 2019, Sarkar et al reported that Co­(acac) 2 can promote the hydrogen auto transfer coupling of o -nitroanilines and primary alcohols to give the corresponding benzimidazoles in decent yields (Scheme c), and the simple cobalt salt catalyst displayed good functional group tolerance.…”
Section: Introductionsupporting
confidence: 91%
“…Recently, there has been a trend toward utilizing earth-abundant metals to construct N-heterocycles under ligand-free conditions . In 2019, Sarkar et al reported that Co­(acac) 2 can promote the hydrogen auto transfer coupling of o -nitroanilines and primary alcohols to give the corresponding benzimidazoles in decent yields (Scheme c), and the simple cobalt salt catalyst displayed good functional group tolerance.…”
Section: Introductionsupporting
confidence: 91%
“…Following this, the reaction mixture was neutralized with 12 mL of 1 M NaOH (aq) , and the resulting aqueous solution was extracted with ethyl acetate (3 × 15 mL), dried with Na 2 SO 4 , and concentrated in vacuo to yield 2-aminopyridine 26 without the need for further purification (50 mg, 96%). Spectral data of 26 matched those previously reported …”
Section: Methodssupporting
confidence: 79%
“…Hence, several efficient nickel complexes have been reported to catalyze N -alkylation reactions. 30 However, to the best of knowledge, there is no report of N -alkylation catalyzed by nickel complex bearing tridentate P3 ligand such as PhP(CH 2 CH 2 PPh 2 ) 2 . Herein, we report the synthesis, and structural characterizations of nickel complexes supported by new tridentate and tripodal tetradentate phosphorus containing ligands along with N -alkylation reactions catalysed by four and five coordinate nickel( ii ) complexes bearing the tridentate P3 ligand.…”
Section: Introductionmentioning
confidence: 99%